2006
DOI: 10.2165/00007256-200636110-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Stretch-Shortening Cycle

Abstract: Neuromuscular fatigue has traditionally been examined using isolated forms of either isometric, concentric or eccentric actions. However, none of these actions are naturally occurring in human (or animal) ground locomotion. The basic muscle function is defined as the stretch-shortening cycle (SSC), where the preactivated muscle is first stretched (eccentric action) and then followed by the shortening (concentric) action. As the SSC taxes the skeletal muscles very strongly mechanically, its influence on the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(172 citation statements)
references
References 121 publications
11
155
0
6
Order By: Relevance
“…3 The stretch-shortening cycle is directly tied to the concept of energy conservation during running; however, it is possible that that the contribution of elastic elements and of yet unestablished reflexes on the inclined plane might be suppressed, 13,28 overloading the skeletal muscle structure. Therefore, the absorption Table 1.…”
Section: Acute Deleterious Mechanisms In Uphill Runningmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The stretch-shortening cycle is directly tied to the concept of energy conservation during running; however, it is possible that that the contribution of elastic elements and of yet unestablished reflexes on the inclined plane might be suppressed, 13,28 overloading the skeletal muscle structure. Therefore, the absorption Table 1.…”
Section: Acute Deleterious Mechanisms In Uphill Runningmentioning
confidence: 99%
“…[3][4][5][6][7] It has also been reported that in race events, mainly in the middle to long distance range, experienced athletes consciously or unconsciously regulate their "pace" strategy in order to maintain a lower metabolic cost. 8,9 However, with the evolution of racing events, it is essential to re-examine models applicable toterrain, including variations positive or negative slopes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Stiffness, as a neural mechanism, depends mostly on the preactivation of the muscles and the action of reflexes: miotatic and Golgi tendon reflex [3,4,8,13]. In light of the biomechanical characteristics, the short-range elastic stiffness is a characteristic for long jump take-off, where it is a matter of an immediate mechanic response of the activated muscle to eccentric contraction.…”
Section: Kinematicsmentioning
confidence: 99%
“…The classification of power is based on different criteria. According to the criterion of action, authors [2,4,7,8,13] distinguish among peak power, explosive power and endurance. Another criterion is that of neuromuscular activity, where power manifests itself in the form of isometric contraction as well as concentric, eccentric or eccentric-concentric contraction.…”
Section: Neuromuscular Mechanisms Of Explosive Powermentioning
confidence: 99%
“…According to the duration of support part, the shortest take-off time was noticed in the take-off of the first -hop -phase (0.12 s) and the longest was the take-off in the last -jump -phase (0.18 s). Eccentric-concentric cycle in the take-off action is a result of muscle-lengthening due to external force and muscle-shortening in the second phase (SSC: stretch -shortening cycle) (Komi, 2000;Komi & Gollhofer, 1997;Nicol, Avela, & Komi, 2006). In eccentric phase a certain amount of elastic energy is stored in the muscular-tendon complex, which can be then used in the second phase.…”
Section: Figurementioning
confidence: 99%